2014
DOI: 10.3109/08880018.2013.874513
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Nucleated Cells, CD34-Positive Cells and CFU-GM Colonies in Single Bone Marrow Samples and Bone Marrow Harvests Derived from Healthy Children

Abstract: Little is known regarding bone marrow (BM) cellularity, CD34+ fraction, and CFU-GM colony formation in relation to age and whether healthy children require a reference range distinct from healthy adults. We therefore analyzed a series of single BM aspirates from 45 healthy children who were evaluated as potential BM donors. Thirty-three of these children subsequently donated BM. We quantified the nucleated cell count, fraction of CD34+ cells, and number of CFU-GM colonies in single aspirates and BM harvests. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
2
13
1
Order By: Relevance
“…Many studies show that regenerative potential of HSC declines. Beside studies describing decrease in HSCs number with age (Kuranda et al 2011;Schündeln et al 2014;Kresnik et al 2016), some other studies reported an increase in HSC number or in the number of HSC subpopulations with age (Kuranda et al 2011;Pang et al 2011). In our count, the concentration of hematopoietic CD45 dim /CD34 ?…”
Section: Discussionsupporting
confidence: 46%
“…Many studies show that regenerative potential of HSC declines. Beside studies describing decrease in HSCs number with age (Kuranda et al 2011;Schündeln et al 2014;Kresnik et al 2016), some other studies reported an increase in HSC number or in the number of HSC subpopulations with age (Kuranda et al 2011;Pang et al 2011). In our count, the concentration of hematopoietic CD45 dim /CD34 ?…”
Section: Discussionsupporting
confidence: 46%
“…For example, evidence has been collected for age-dependent deterioration of the proliferative capacity of BM-derived progenitor cells and in general the hematopoietic compartment [ 24 ]. In healthy subjects and/or CAD patients, age has been associated with impaired in vivo neovascularization, in vitro migration, and myeloid differentiation capacity of BM-MNC [ 14 , 40 ]. This age effect was also observed in our study population: a negative relation was found with both GM-CFU and BFU-E numbers; however, this bias was limited since our study cohorts did not differ with respect to age.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our ndings (higher cell counts in younger patients) support a previous study with a smaller sample size. 6 Autologous BM-derived cell-based therapies in regenerative medicine are on the rise. While it is generally known that BMA contains a mix of nucleated cells and other biologics such as growth factors and exosomes 13 , comprehensive information regarding normal ranges of leucocytes and/or CD 34 + cell counts in BMA and BMAC in a large series of patients of all age groups was missing.…”
Section: Discussionmentioning
confidence: 99%